1998
DOI: 10.1002/(sici)1099-1395(199806)11:6<378::aid-poc987>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio and molecular mechanics (MM3) calculations on alkyl- and arylboronic acids

Abstract: The boronic acid functional group has been incorporated into various biologically important compounds. In order to study this class of compounds better with molecular mechanics, five alkyl-and arylboronic acids were calculated using ab initio methods (Spartan) at the RHF/6-31G * level. MM3 force field parameters were developed based on the theoretically calculated geometries, vibrational spectra, and torsional profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…But by using HF/6-31G(d) levels of theory, for a few boronic acids including the phenylboronic acid molecule Chen et al found approximately same value for this bond length. [34] Bond angles at B and C are consistent with sp 2 hybridization but with significant deviations from the expected 120 • angles occurring in close proximity the -B(OH) 2 substituent on C 4 atoms for 4Clpba and 4Brpba.…”
Section: Geometrical Structuresmentioning
confidence: 77%
“…But by using HF/6-31G(d) levels of theory, for a few boronic acids including the phenylboronic acid molecule Chen et al found approximately same value for this bond length. [34] Bond angles at B and C are consistent with sp 2 hybridization but with significant deviations from the expected 120 • angles occurring in close proximity the -B(OH) 2 substituent on C 4 atoms for 4Clpba and 4Brpba.…”
Section: Geometrical Structuresmentioning
confidence: 77%
“…[6] The boronic acid moiety has also been incorporated into amino acids and nucleosides as antitumor, antiviral agents. [7] Phenylboronic acid is a versatile building block in organic synthesis and an important intermediate in the synthesis of active compounds in agrochemical and pharmaceutical industries. [8] In order to study these biologically important type of molecules by density functional theory (DFT) methods, the necessary parameters had to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…[13] The boronic acid moiety has been incorporated into amino acids and nucleosides as anti-tumor and anti-viral agents. [14] It's noted that vibrational spectra of arylboronic acid were reported by Santucci and Gilman. [15] Faniran and Shurvell [16] have assigned the infrared spectra of phenylboronic acid and deuterated phenylboronic acid.…”
Section: Introductionmentioning
confidence: 99%